2010
DOI: 10.1111/j.1751-553x.2010.01231.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of malaria and the comparison of hematological and biochemical indices of Plasmodium falciparum‐parasitemic and aparasitemic sickle cell disease (SCD) patients

Abstract: Hemolytic anemia is common in sickle cell disease (SCD), but the course and extent differ, depending on genetic, epigenetic, and environmental factors. In the malaria-endemic tropical environment, some vulnerable subjects would be infected and the impact of infection would vary. Therefore, this study was to find malaria incidence and the associated changes in some laboratory indices in 330 SCD subjects. Following blood smear preparation for falciparum detection, hematological and biochemical indices were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The corresponding profiles for the SCD subjects are also similar to reported values for SCD subjects [58]. …”
Section: Discussionsupporting
confidence: 82%
“…The corresponding profiles for the SCD subjects are also similar to reported values for SCD subjects [58]. …”
Section: Discussionsupporting
confidence: 82%
“…Both M111.0 expression and leukocyte count, but not IP-10, negatively predicted reticulocyte-specific expression. Consistent with chronic, compensated hemolysis seen in sickle cell anemia [29], HbSS status predicted higher reticulocyte-gene expression relative to CM after controlling for other factors.…”
Section: The Interferon Response Negatively Predicts Reticulocyte-spementioning
confidence: 54%
“…[6] The mean total white blood cell count (WBC) in this study were similar to other earlier studies. [2,6,7] Studies reported rise in TLC in patients of SCD, as compared to control groups. But in our study, it was not statistically significant (>0.05).…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, patients with SCD suffer repeated vasoocclusive events characterized by ischemia-reperfusion injury and inflammation, in which red blood cells (RBCs) and white blood cells (WBCs) play a key role. [2] Although red cell sickling is more prominent during crisis, continuous sickling does occur at a lower rate in the steady state. Hence, a certain proportion of sickled cells are always present in the circulation of SCA patients even in steady state.…”
Section: Introductionmentioning
confidence: 99%